Melanochelys trijuga (Schweigger 1812) –Indian Black Turtle - Das, Indraneil; Bupathy, S. (Chelonian Research Foundation, 2009)
The Indian black turtle, Melanochelys trijuga (Family Geoemydidae), is a medium-sized (carapace length to 38.3 cm), mainly still-water species from northern, northeastern, and peninsular India, Sri Lanka, Myanmar, Nepal, Bangladesh, Thailand, and possibly Pakistan. Six subspecies are currently recognized. The turtle has been introduced to some of the islands of the western Indian Ocean by seafarers. Omnivorous in dietary habits, the species takes aquatic plants in addition to invertebrates and carrion. Two to 16 elongated, brittle-shelled eggs are laid, with eggs and hatchlings showing considerable size variation. The species, although in no immediate danger in India, is exploited in unknown numbers for food, and population declines have been reported from Sri Lanka.